Significance of Lorentz forces on Jeffrey nanofluid flows over a convectively heated flat surface featured by multiple velocity slips and dual stretching constraint: a homotopy analysis approach. Issue 2 (21st March 2022) - Dawar, Abdullah; Wakif, Abderrahim; Saeed, Anwar; Shah, Zahir; Muhammad, Taseer; Kumam, Poom
Abstract: Motivated by the temporal relaxation feature of the Jeffrey model and its practical uses in the rheological modeling of several vital liquids, this study aimed to present a theoretical analysis of three-dimensional MHD Jeffrey nanofluid flows over a dual stretching surface with velocity slip conditions. By adopting the nonhomogeneous nanofluid model along with the passive control approach of nanoparticles, the current flow problem is solved semi-analytically via the homotopy analysis method for convective heating and multiple slip conditions. Dynamically, the magnetic and viscoelastic parameters have a declining effect on the velocity distributions in both directions in the existence and absence of slip effects, while the Deborah number has generally an escalating influence on the flow distributions. On the other hand, the variations of the velocity profiles in both directions are always greater in the presence of slip effect as compared to the nonslip case. Besides, the velocity stretching factor rises the velocity profiles in both directions. Furthermore, this increasing impact is dominant for the velocity distribution along the y- direction as compared to the velocity field along the x- direction. Thermally, the greater Biot number increases the temperature distribution. However, the bigger Schmidt number reduces the concentration distribution. Graphical Abstract: